Bond Graph Modeling of Muscle-Tendon Actuation of a Phalange - Uppal, Sandeep Kumar; Vaz, Anand (Computer Assisted Methods in Engineering and Science, 2022)
In musculoskeletal actuation systems, it is essential to understand and analyze the extension and force patterns generated in the muscle-tendon units (MTUs) responsible for the motion of a phalange. This work proposes a systematically developed bond graph model for the muscle-tendon actuation system for the desired motion of the phalange of the hand. The phalange is represented by a cylindrical rigid body, actuated by four MTUs attached to it symmetrically. The MTU is based on Hill’s muscle model. The role of the central nervous system (CNS) that commands desired motions to the phalange is emulated through a virtual domain in the model. The virtual domain decides the activation pattern of MTUs. Accordingly, the MTUs apply forces on the phalange to achieve the desired motion. Simulation results for important motions such as flexion-extension, adductionabduction, and circumduction show that the model effectively captures the dynamics of the musculoskeletal actuation system.